Human rights, justice, and constitutional empowerment - Raj Kumar, C.; Chockalingam, K.; Krishna Iyer, V. R., 1915- (New Delhi ; New York : Oxford University Press, 2007)
Contributed articles with primary focus on India; commemorative volume for Justice V.R. Krishna Iyer, b. 1915
Includes bibliographical references
Keywords: Civil rights -- India